Early and late‐onset veno‐occlusive disease/sinusoidal syndrome post allogeneic stem cell transplantation – a real‐world UK experience. Issue 2 (20th November 2020) - Mehra, Varun; Tetlow, Simon; Choy, Adrian; de Lavallade, Hugues; Kulasekararaj, Austin; Krishnamurthy, Pramila; Avenoso, Daniele; Marsh, Judith; Potter, Victoria; Mufti, Ghulam; Pagliuca, Antonio; Gandhi, Shreyans
Abstract : Classical veno‐occlusive disease/sinusoidal obstruction syndrome (VOD/SOS) is a serious complication post allogeneic hematopoietic stem cell transplantation (HSCT). Before the recently revised EBMT criteria, the Baltimore and modified Seattle criteria failed to recognize the syndrome of late‐onset VOD. We present real‐world experience from a large UK transplant center reporting on VOD/SOS in consecutive HSCT adult patients (n = 530), transplanted for hematological cancers. We identified 27 patients treated with Defibrotide for VOD/SOS diagnosis, where detailed data were available for final analysis. Using standard definitions including EBMT criteria, around 30% (n = 8/27) of cases classified as late‐onset VOD presenting at median of 46 (22‐93) days but with D100 survival (63% vs 58%, Log‐rank; P = 0.81) comparable to classical VOD. Hazard ratio for D100 mortality was 2.82 (95% CI: 1.74‐4.56, P  < .001, Gray test) with all VOD/SOS events. Twenty percent (n = 2/8) of late‐onset VOD patients were anicteric and 42% (n = 8) classical VOD patients presented with refractory thrombocytopenia, while less than half met EBMT criteria for classical VOD in adults, highlighting gaps in real‐world diagnostic limitations using EBMT criteria. However, challenges remain about underrecognition and difficulties related to early defibrotide access for treatment of late‐onset VOD in current treatment guidelines. Our report strongly supports early Defibrotide for the treatment of severe VOD/SOS in adults regardless of time of onset. Abstract : Late‐onset veno‐occlusive disease, defined as occurring beyond 21 days after allogeneic haematopoietic stem cell transplant, remains a significant yet under‐recognized problem, accounting for nearly one‐third of cases and showing equivalent outcomes following defibrotide treatment compared to the classic form.